2021
DOI: 10.1302/2633-1462.211.bjo-2021-0143
|View full text |Cite
|
Sign up to set email alerts
|

Open MRI assessment of anterior femoroacetabular clearance in active and passive impingement-provoking postures

Abstract: Aims Cam and pincer morphologies are potential precursors to hip osteoarthritis and important contributors to non-arthritic hip pain. However, only some hips with these pathomorphologies develop symptoms and joint degeneration, and it is not clear why. Anterior impingement between the femoral head-neck contour and acetabular rim in positions of hip flexion combined with rotation is a proposed pathomechanism in these hips, but this has not been studied in active postures. Our aim was to assess the anterior impi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This is in accordance with the results of the current study that analyzed subgroups with different hip morphologies. The results of the current study are in line with another recent study of patients with cam or pincer morphologies, which evaluated hip impingement conflict in flexion using open MRI, 44 scanning hips in active squatting and passive sitting position. However, another study found that cam resection (femoral neck osteochondroplasty) improved postoperative flexion by 8° in a sitting posture, 45 analyzing a small sample size.…”
Section: Discussionsupporting
confidence: 89%
“…This is in accordance with the results of the current study that analyzed subgroups with different hip morphologies. The results of the current study are in line with another recent study of patients with cam or pincer morphologies, which evaluated hip impingement conflict in flexion using open MRI, 44 scanning hips in active squatting and passive sitting position. However, another study found that cam resection (femoral neck osteochondroplasty) improved postoperative flexion by 8° in a sitting posture, 45 analyzing a small sample size.…”
Section: Discussionsupporting
confidence: 89%
“…Values of LCEA > 39° indicate pincer type impingement, and values < 25° are suggestive of acetabular dysplasia [27]. Values of alpha angle ≥ 60° indicate cam morphology [28]. The Tönnis classification (Table 1) was used to evaluate the degree of osteoarthritis [29].…”
Section: Eligibility Criteriamentioning
confidence: 99%